PENGARUH PERMAINAN CONGKLAK TERHADAP KEMAMPUANBERHITUNG ANAK USIA 5-6 TAHUN DI TK BINA ASUHANDESAMAYANG PONGKAI KECAMATAN KAMPAR KIRI TENGAH - Darliati Darliati '; Wilson Wilson '; Nurlita Nurlita ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to determine the numeracy skills of children in Bina Asuhan kindergarten Mayang Pongkai village before and after the congklak game used, also to find out if there is a significant impact on numeracy skills of children aged 5 -6 years in Bina Asuhan kindergarten before and after the congklak game used. The population and sample in this study were 14 childrens. Data collection techniques used was interviews. Data analysis techniques in this study are using t-test formula. From the research, the numeracy skills of children aged 5-6 years in Bina Asuhan kindergarten Mayang Pongkai Village Left Central Kampar District before being given treatment largely classified in the category of low, means that desperately need guidance from teachers to improve the numeracy skills. Numeracy skills of children in Bina Asuhan kindergarten after the treatment is given the form of implementation congklak game included in the high category, it means numeracy skills of children are developed according to expectations. Implementation of congklak games activities have a positive influence on numeracy skills of children aged 5-6 years in Bina Asuhan kindergarten Mayang Pongkai Village Central-Left Kampar Distric.Keywords: Numeracy Skills, Congklak Games